2015
DOI: 10.1111/ijlh.12408
|View full text |Cite
|
Sign up to set email alerts
|

Leishman and Giemsa stain: a new reliable staining technique for blood/bone marrow smears

Abstract: L&G staining is a newer staining technique of immense help in high-throughput haematology laboratories by offering a time-saving, cost-effective and better staining option to conventional staining methods. It gives a better nuclear and cytoplasmic differential staining and can also be used in automated blood counters/stainer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…The number of megakaryocytes in a 1.5×3.5-cm area of a standard bone marrow smear were determined under microscope (BX53; Olympus Corporation, Tokyo, Japan) using Wright's staining (Sigma-Aldrich, St. Louis, MO, USA) in all patients and donors, as described previously ( 17 , 18 ). Megakaryocyte morphology was also analyzed in all patients and donors ( 17 , 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…The number of megakaryocytes in a 1.5×3.5-cm area of a standard bone marrow smear were determined under microscope (BX53; Olympus Corporation, Tokyo, Japan) using Wright's staining (Sigma-Aldrich, St. Louis, MO, USA) in all patients and donors, as described previously ( 17 , 18 ). Megakaryocyte morphology was also analyzed in all patients and donors ( 17 , 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…Extensive studies based on the cytoplasmic and nuclear characteristics associated with periodontitis have not been done elsewhere. Gjendra et al 27 reported that LG combination gives better nuclear morphology, crisp nuclear and cytoplasmic contrast, staining of cytoplasmic granules, and metachromasia to the background material in hematological samples. These staining characteristics of LG cocktail stain were utilized in this study for the assessment and grading of the inflammatory features of the epithelial cells associated with periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Well-stained blood film is very important for right cell structure assesment. There are some tried staining techniques like Leishman and Giemsa to dye various smears [14]. Authors' work is upon trying of a plant dye in blood cells.…”
Section: Discussionmentioning
confidence: 99%